2016
DOI: 10.2215/cjn.01730215
|View full text |Cite
|
Sign up to set email alerts
|

Association between Serum Potassium and Outcomes in Patients with Reduced Kidney Function

Abstract: Background and objectives Patients with CKD are more likely than others to have abnormalities in serum potassium (K + ). Aside from severe hyperkalemia, the clinical significance of K + abnormalities is not known. We sought to examine the association of serum K + with mortality and hospitalization rates within narrow eGFR strata to understand how the burden of hyperkalemia varies by CKD severity. Associations were examined between serum K + and discontinuation of medications that block the renin-angiotensin-al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
227
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(253 citation statements)
references
References 18 publications
(17 reference statements)
22
227
2
2
Order By: Relevance
“…Similarly, Hayes et al [40] evaluated a cohort of pre-dialysis CKD male patients ( n = 1,227) and found that serum K + of <3.6 mEq/L was associated with faster CKD progression compared to serum K + of 3.6-5.5 mEq/L. Several other studies demonstrated a significant association of serum K + <4.0 mEq/L and mortality, but the index of inflammation and follow up on CKD progression were not evaluated in sufficient detail [41][42][43] . Collectively, consistent with prior studies in animal CKD models [44] and known information of hypokalemia being a stimulator for ammonium genesis, angiotensin II, inflammatory mediators, and oxidative stress [28,45] , even mild degrees of hypokalemia, 3.5-4.0 mEq/L (which may be considered "normal") in patients with CKD can induce inflammation and poor clinical outcomes.…”
Section: Hypokalemiamentioning
confidence: 99%
“…Similarly, Hayes et al [40] evaluated a cohort of pre-dialysis CKD male patients ( n = 1,227) and found that serum K + of <3.6 mEq/L was associated with faster CKD progression compared to serum K + of 3.6-5.5 mEq/L. Several other studies demonstrated a significant association of serum K + <4.0 mEq/L and mortality, but the index of inflammation and follow up on CKD progression were not evaluated in sufficient detail [41][42][43] . Collectively, consistent with prior studies in animal CKD models [44] and known information of hypokalemia being a stimulator for ammonium genesis, angiotensin II, inflammatory mediators, and oxidative stress [28,45] , even mild degrees of hypokalemia, 3.5-4.0 mEq/L (which may be considered "normal") in patients with CKD can induce inflammation and poor clinical outcomes.…”
Section: Hypokalemiamentioning
confidence: 99%
“…The 1-day-mortality ratio was increased significantly in hospitalized patients with serum K levels above 5.5 mEq/L [17]. In a retrospective study with non-dialyzed CKD patients, when patients were followed for an average of 2.76 years, both hypokalemia and hyperkalemia were found to have a strong, independent, and statistically significant association with mortality, major cardiovascular events, and increased incidence of hospitalization [23].…”
Section: Discussionmentioning
confidence: 95%
“…There is a U-shaped relationship between serum K level and mortality, both low and high serum K values are associated with mortality [16,23,24]. Significant associations were found between hyperkalemia and increased risk of mortality and arrhythmia in observational studies [17,23,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adjusted mortality for patients with a serum potassium >6 mmol/l was 3.08 (2.17-4.37), MACE 2.11 (1.68-2.65) and discontinuation of RAS blockade 1.81 (1.45-2.26) in comparison to patients with potassium <6 mmol/l [82]. …”
Section: Are Acei/arbs Cardioprotective?mentioning
confidence: 99%